Deconstructing the right to safe drinking water in Peru: new challenges at our two hundred years as a Republic - Matayoshi Collazos, Andres (2021)
In 2017, the right of potable water was incorporated in our Constitution. This research seeks to identify the problem of the realization of the right to potable water in the peruvian reality and the normative impact from its incorporation in the Constitution, with an emphasis on the current situation in the context of the pandemic caused by COVID-19.  An analysis will be made of the role of rights in the model of Constitutional State Governed by Rule of Law, as well as of international standards and comparative experience at both the normative and jurisprudential levels. Finally, public policies and the normative and jurisprudential development of the right to potable water in Peru will be developed, culminating in the proposal to establish a constitutionally protected minimum of the right to potable water as a formula for its realization.